[PP.25.43] CHANGES OF INTRINSIC STIFFNESS OF THE CAROTID ARTERIAL WALL DURING THE CARDIAC CYCLE MEASURED BY SHEAR WAVE ELASTOGRAPHY IN HYPERTENSIVES COMPARED TO NORMOTENSIVES. (September 2017) - Marais, L.; Pernot, M.; Khettab, H.; Tanter, M.; Messas, E.; Zidi, M.; Laurent, S.; Boutouyrie, P.
Abstract : Objective: The question whether arterial stiffness in hypertension is increased solely because of increased arterial pressure is not solved. Because measurement of arterial stiffness is highly dependent on measurement of blood pressure (BP), the development of methods independent of BP is necessary for clarifying this question. Shear wave elastography (SWE, Supersonic Imagine, Aix-en-Provence, France) is an ultrasound technique which enables to quantitatively assess local tissue stiffness by remotely generating transient shear waves into the tissue (push mode) and tracking their propagation using a very fast sampling rate (up to 10 kHz). The elastic modulus of the material is directly related to the speed of the shear waves, with no need of BP. This method has never been tested against classical echotracking (Artlab, Esaote, Maastricht, NL) and carotid to femoral pulse wave velocity (cf-PWV, Sphygmocor, AtCor, Sydney, Australia). Design and method: We included 25 subjects, 14 normotensives (NT) and 11 essential hypertensives (HT), matched for age and sex. We compared SWE to echotracking and cf-PWV. We optimized SWE algorithms for carotid wall tracking and shear wave group velocity calculation for the anterior (a-SWV) and posterior wall (p-SWV). 8 ultrasonic pushes were triggered at intervals of 200 ms in order to study the variations of stiffness during the cardiac cycle. Results: p-SWV showed no association with carotid PWV, cf-PWV nor BP. Mean a-SWV over the cardiac cycle is strongly associated with carotid PWV measured by Echotracking (r = 0.56, p = 0.003) and cf-PWV (r = 0.66, p < 0.001). a-SWV strongly increases with BP level during the cardiac cycle (p < 10–6). Similar associations between a-SWV and BP were found in NT and HT although HT had higher values of a-SWV throughout all BP levels. However, when a common BP value (100 mmHg) was considered, no significant difference was found between NT and HT, therefore showing that the wall intrinsic material stiffness is not increased in HT. Conclusions: We have demonstrated with a method independent of BP that the increased arterial stiffness in HT is entirely due to the BP increase. SWE appears as a promising technique for assessing arterial stiffness.